JENIS DAN KARAKTERISTIK HUKUM PIDANA DI INDONESIA - Krismen, Yudi; Fatimah, Aisyah; Oktavia, Intan; Al Rasyid, Franzee (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Criminal law in Indonesia has undergone significant development in response to the increasing complexity of modern crimes, which can no longer be effectively addressed by the provisions of the Criminal Code (KUHP). This study aims to analyze the types of criminal law in force in Indonesia, identify the characteristics of special criminal law as a response to extraordinary crimes, and examine corporate liability within the framework of special criminal law. The research method employed is normative legal research using a legislative and conceptual approach. The results indicate that Indonesian criminal law is divided into general criminal law and special criminal law, where special criminal law serves as an adaptive criminal policy instrument against transnational crimes such as corruption, narcotics, money laundering, human trafficking, terrorism, and cybercrime. The characteristics of special criminal law are marked by deviations from general criminal procedure law, a reversal of the burden of proof, and the ability to hold corporations liable as perpetrators of criminal acts. This study concludes that special criminal law is not merely a supplement to the Criminal Code (KUHP), but a main pillar of contemporary Indonesian criminal law policy.